Electives shopping, grading competition, and grading norms - Martin Gregor (Charles University in Prague, Institute of Economic Studies (IES), 2018)
This paper analyzes grading competition between instructors of elective courses when students shop for high course scores, the instructors maximize class size, and the school imposes a ceiling on mean course scores to limit grade inflation. Under this grading norm, we demonstrate that curriculum flexibility (more listed courses or less required courses) intensifies the competition: in particular, both top and mean realized scores increase. To tame incentives to provide excessively large scores, we suppose that the school additionally introduces a top-score grading norm. We consider three scenarios. First, the school caps top scores directly. Then, grading competition divides students into a concentrated group of achievers and a dispersed group of laggards. Second, the school normalizes the range of scores by changing the mean-score ceiling. Upon normalization, scores of a less flexible curriculum first-order stochastically dominate scores of a more flexible curriculum. Hence, all students will prefer rigid curricula. Third, the school requires that the mean-score ceiling is evaluated for enrolled students instead of all students. Then, the instructors stop competing for students which introduces sorting inefficiencies. Overall, we show that addressing grade inflation through grading norms may generate inequalities, rigidities, and inefficiencies.
Keywords: C72; D02; D21; I21; I23; 330; grading competition; grades compression; grading norms; Continuous Lotto games; Captain Lotto games; higher education